Motivation Level Akit Tribe Fishermen Bantan Air Village Bantan District Bengkalis Regency Riau Province - Lambas Sitompul; Ridar Hendri; Lamun Bathara (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was conducted on July 2013 in Bantan Air village Bantan District Bengkalis Regency of Riau Province. This study aimed to describe the fishing effort (including age, education, number of dependents ,income ,business experience, and fishing effort of Akit Tribe), motivation level and the relationship between motivation level to business endeavor. This research used survey method. To get respondents this research used accidental sampling. To determine motivation level were measured by Likert scale and to determine relationship between level of fishing effort to motivation level used Contingencies Correlation Coefficient then was analized by SPSS version 17. Overall motivation level was in moderate category. This condition was caused by low expectations and lack of confidence in carrying fishermen fishing effort .Keyword : Akit Tribe, motivation, Contingencies Correlation Coefficient